Aging of the T cell compartment in mice and humans: from no naïve expectations to foggy memories - Nikolich-Žugich, Janko (2014)
Until the mid-20(th) century, infectious diseases were the major cause of morbidity and mortality in humans. Massive vaccination campaigns, antibiotics, antivirals and advanced public health measures drastically reduced sickness and death of infections in children and younger adults. Older adults (>65yr of age), however, remain vulnerable to infections, and to date infectious diseases remain amongst the top 5–10 causes of death in this population. The aging of the immune system, often referred to as immune senescence, is the key phenomenon underlying this vulnerability. This review centers on age-related changes in T cells, which are dramatically and reproducibly altered with aging. I will discuss changes in T cell production, maintenance, function and response to latent persistent infection, particularly against the cytomegalovirus (CMV), that exerts profound influence on the aging T cell pool, concluding with a brief list of measures to improve immune function in older adults.